The Reality of Intellectual Compatibility Between Spouses and Its Relationship to Self-Efficacy Among Saudi Working Wives - Hakami, Huda Musa; Malibari, Najat Abdullah (Journal of Humanities & Social Sciences, 2025)
This study aimed to examine the level of intellectual compatibility between spouses and its relationship to self-efficacy among a sample of working wives. The sample consisted of 380 Saudi working wives residing in the city of Jeddah. To achieve the study objectives, the descriptive correlational method was employed. A research instrument was developed to collect data, consisting of two questionnaires: the Intellectual Compatibility Between Spouses Questionnaire, which includes three dimensions (marital problem-solving, intellectual rigidity, and shared goals), and the Self-Efficacy Questionnaire, which includes three dimensions (behavioral initiative, effort, and perseverance). The validity and reliability of the instrument were confirmed using Cronbach’s Alpha and Pearson’s correlation coefficient.The results revealed that the level of intellectual compatibility between spouses was moderate among the study sample, with a mean score of (3.32) out of (5). while the level of self-efficacy was found to be high, with a mean score of (4.08) out of (5). Furthermore, a statistically significant positive correlation was identified between intellectual compatibility and self-efficacy among the participants. The study concluded with several recommendations, including integrating the concept of intellectual compatibility into premarital counseling programs organized by the Ministry of Social Affairs or family counseling centers, and incorporating the concept of self-efficacy into support programs for working women, in a way that enhances their adaptability and ability to achieve work–life balance.
Keywords: Intellectual compatibility between spouses; self-efficacy; Saudi working wives